Effect of Bruguiera gymnorrhiza Leaf Extract on malondialdehyde (MDA) Levels and Pancreatic Histopathology in Diabetic Mice - Makwa, Jannatul; Purnama, Erlix Rakhmad (LenteraBio : Berkala Ilmiah Biologi, 2024)
Diabetes mellitus causes an increase in malondialdehyde levels and pancreatic ? damage in the body. Mangrove leaf extract (Bruguiera gymnorrhiza) has bioactive compounds to decrease MDA levels and repair pancreatic ? cells. This study aimed to determine the effect of Bruguiera gymnorrhiza leaf extract on malondialdehyde levels and pancreatic ? cells. This study used 24 mice divided into 6 groups: control group, positive control (alloxan induction and glibenclamide treatment), negative control (alloxan induction without treatment), 200 mg/kgBB dose, 400 mg/kgBB dose, and 600 mg/kgBB dose group. MDA levels in mice serum were measured using the TBARS method, and pancreatic ?-cells were analyzed using the scoring method. Data analysis used descriptive analysis for MDA levels of mice, the Kruskall-Wallis, and the Mann-Whitney tests used for scoring data analysis of pancreatic ?-cell damage. The results showed that a dose of 400 mg/kgBB was the best dose to reduce MDA levels, and a dose of 600 mg/kgBB was the best in repairing pancreatic ? cells. The conclusion of this study is that mangrove leaf extract (Bruguiera gymnorrhiza) has an effect in reducing MDA levels and repairing pancreatic ? cells in diabetic mice.